SOCIAL NETWORKING ADDICTION AMONG ADOLESCENT HOSTEL STUDENTS: A DESCRIPTIVE STUDY (CAHIERS MAGELLANES-NS, 2024)
This descriptive study examines the level of social network addiction among the Adolescent Hostel students. The universe of the present study consists of 118 adolescent students (81 girls and 37 boys) staying in a hostel. Census method was adopted and the data was collected from all the 118 Adolescent hostel students.  To measure the social network addiction of the Adolescent Hostel students the researcher used the social media addiction scale by Aylin TUTGUN-UNAL, Levent DENIZ (2015). The study findings revealed most of the respondents are using mobile phones frequently and have scored high level in social network addiction and there is significant difference between sex, order of birth, frequency of using mobile etc.